Trends in business strategy research, bibliometric analysis and text mining - Dvorak, Jiri; Tripes, Stanislav; Sokolova, Marcela; Musilova, Iveta (Journal of Business Economics and Management, 2022)
This study aims to contribute to the systematisation of knowledge in the field of business strategies and analyse its trends. An initial dataset of 884 articles was extracted from the WoS and Scopus databases based on keywords. This dataset was reduced to 430 articles by detailed reading and processed through bibliometric analysis and text mining. The bibliometric analysis confirmed an increasing number of articles, unbalanced contributions of individual journals, and unbalanced citation rates by articles and authors. Textmining analysis showed the dominance of Porter’s generic strategies and Miles and Snow’s typology of strategies. The results show that the theory of business strategy is not subject to trends and has not yet been significantly affected by changes in real business, thus creating opportunities for future research. This study addresses the gap in the comprehensive review of trends in business strategy development.